Impaired coronary flow reserve immediately after coronary angioplasty in patients with acute myocardial infarction. Issue 4 (April 1993) - Ishihara, M; Sato, H; Tateishi, H; Kawagoe, T; Yoshimura, M; Muraoka, Y
Abstract : OBJECTIVE--To examine coronary flow reserve immediately after emergency coronary angioplasty in patients with acute myocardial infarction. DESIGN--A 3 F coronary Doppler catheter was used to measure coronary blood flow velocity in the infarct artery and in the non-infarct artery. Maximal hyperaemia was produced by 10 mg of intracoronary papaverine and coronary flow reserve was calculated. PATIENTS--11 patients with acute myocardial infarction undergoing both emergency coronary angioplasty (4.7 (3.6) h after the onset of chest pain (mean (SD))) and at follow up catheterisation 16 (4) days after angioplasty. SETTING--Hiroshima City Hospital. RESULTS--There was no stenosis of > or = 50% in the coronary artery of interest. Immediately after coronary angioplasty the mean (1 SD) coronary flow reserve of the infarct artery was significantly less than that of the non-infarct artery (1.4 (0.4) v 2.8 (0.8), p < 0.001). At follow up catheterisation the coronary flow reserve of the infarct artery increased almost to the value of the non-infarct artery (2.8 (1.2) v 3.1 (0.8) p = NS). CONCLUSION--The coronary flow reserve in the infarct region was severely impaired immediately after reperfusion, even with a widely patent infarct artery. This could restrict the beneficial effects of reperfusion therapy, especially when there is a severe residual stenosis.